2016
DOI: 10.1097/mej.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Testicular torsion and the acute scrotum: current emergency management

Abstract: The acute scrotum is a challenging condition for the treating emergency physician requiring consideration of a number of possible diagnoses including testicular torsion. Prompt recognition of torsion and exclusion of other causes may lead to organ salvage, avoiding the devastating functional and psychological issues of testicular loss and minimizing unnecessary exploratory surgeries. This review aims to familiarize the reader with the latest management strategies for the acute scrotum, discusses key points in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
0
24
0
3
Order By: Relevance
“…Similarly, Doppler ultrasound also has its advantages of excellent imaging of anatomical details and perfusion, high availability, short duration, and low costs. 11 However, there are two key limitations of Doppler in the diagnosis of testicular torsion especially in infants and children, that is, the high false-negative rate and high operator dependency, 12 , 13 especially in emergency settings. Also, our ultrasound specificity was only 71.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Doppler ultrasound also has its advantages of excellent imaging of anatomical details and perfusion, high availability, short duration, and low costs. 11 However, there are two key limitations of Doppler in the diagnosis of testicular torsion especially in infants and children, that is, the high false-negative rate and high operator dependency, 12 , 13 especially in emergency settings. Also, our ultrasound specificity was only 71.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In two separate studies, Scarabelli et al and The 720-degree rotation is called complete spermatic cord torsion, and an experimental animal study has shown that this degree of torsion causes irreversible ischaemic damage and gonadal loss in the testis within 2 hr (Asgari et al, 2006). In some series, it was reported that testicular torsions on the left side were more common than the TA B L E 2 Comparison of MDA, SOD and CAT values of the groups in pairs, and Johnsen Testicular Biopsy Score (JTBS) values of groups in pairs F I G U R E 1 a. Spermatids (↑) and spermatozoa (▲) in testis of control group, b. a small number of ghost germinal epithelial cells were observed in the left testis tubule lumen of the torsion/ detorsion group (▲), and c. spermatids (↑) and spermatozoa (▲) in testis of Group 3 right (Ta et al, 2016). In this study, we preferred 720-degree torsion and 2-hr reperfusion to the left testis.…”
Section: Discussionmentioning
confidence: 99%
“…On physical examination, a high-riding testis, an abnormally oriented testis, and absent cremasteric reflexes should raise suspicion of TT. The cremasteric reflex is elicited when the medial aspect of the thigh is stroked, leading to the contraction of the cremasteric muscle and thus resulting in the elevation of the testis [6]. In TAT, the necrotic appendix can be observed through the scrotum, giving rise to the blue dot sign.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory investigations can be performed to rule out other possible etiologies. Nevertheless, clinicians must not depend exclusively on clinical findings since they are not absolute in yielding a definitive diagnosis, and misdiagnosis of TT can lead to exceedingly adverse disease outcomes such as gangrene of the testis [6][7][8]. Murphy et al reported three cases of patients with a normal cremasteric reflex requiring orchidectomy [7].…”
Section: Discussionmentioning
confidence: 99%